2021
DOI: 10.15561/26649837.2022.0101
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of proprioceptive neuromuscular facilitation stretching, massage and combine protocols on flexibility, vertical jump and hand grip strength performance in kickboxers

Abstract: Background and Study Aim. Strength, power and flexibility are among the features that provide advantage against the opponent in kick boxers. There are many factors that can affect the development of these parameters in a positive and negative way before the competition. These factors may differ according to the type and intensity of warm-up and stretching exercises, depending on psychological and physiological conditions. The aim of this study is to evaluate the effects of proprioceptive neuromuscular facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…There was find a significant main effect for flexibility, countermovement jump and squat jump performance of muay thai athletes [ 76 ]. Eken and Bayer [ 77 ], had evaluated the effects of proprioceptive neuromuscular facilitation (PNF) stretching, massage, PNF + massage on flexibility, vertical jump and hand grip strength performance in kickboxers. They found that, there was a significant difference between PNF and PNF + M, M and PNF + M in favour of PNF + M in vertical jump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was find a significant main effect for flexibility, countermovement jump and squat jump performance of muay thai athletes [ 76 ]. Eken and Bayer [ 77 ], had evaluated the effects of proprioceptive neuromuscular facilitation (PNF) stretching, massage, PNF + massage on flexibility, vertical jump and hand grip strength performance in kickboxers. They found that, there was a significant difference between PNF and PNF + M, M and PNF + M in favour of PNF + M in vertical jump.…”
Section: Discussionmentioning
confidence: 99%
“…They found that, there was a significant difference between PNF and PNF + M, M and PNF + M in favour of PNF + M in vertical jump. They found a significant decrease in right- and left-hand grip strength for all protocols [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…While considering the constraints of the sustainability of scarce natural resources, recreational activities should be planned to meet the needs of especially middle-aged users [1][2][3][4][5][6] . These are individuals who have either completed their working life or stopped working, who want to relax and enjoy their old age.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the parameters of healthy life, physical and psychological quality of life of people improves due to massage and different recovery methods after exercise. However, due to different reasons, negative situations occur in the quality of life of people [1][2][3] . For example; The COVID-19 pandemic has had devastating effects on our lives, mental health, and lifestyle.…”
Section: Introductionmentioning
confidence: 99%